The Possibilities of Thromboelastography in Assessing Safety of Neuraxial Blocks in Gestational Thrombocytopenia (Clinical Study) - E. N. Plakhotina; T. N. Belousova; N. B. Kuzina; A. N. Kuzovlev; E. V. Bryantsev (Неотложная медицинская помощь)
Gestational thrombocytopenia (GT) is the most common type of thrombocytopenia during pregnancy. Unlike other types of thrombocytopenia, it is not accompanied by dysfunction of the cellular component of hemostasis. Currently, a quantitative decrease in platelets in GT is a contraindication to neuraxial blockades (NAB), which significantly reduces the quality of care in childbirth.The aim of the study is to determine the possibility of safe use of neuraxial blockades in gestational thrombocytopenia. A retrospective prospective study involved 70 patients who were performed delivery, depending on obstetric indications, either conservatively or surgically. The patients were divided into two groups. The main group (group No. 1) included 35 patients with gestational thrombocytopenia. The comparison group (group No. 2) consisted of 35 patients with a platelet content above 150×109/l. A comparative intergroup analysis of indicators of a general blood test, coagulogram, thromboelastography with a test for functional fibrinogen before childbirth and 2 days after delivery. The change in platelet content and its effect on the coagulation status of patients during pregnancy were retrospectively analyzed. A comparative assessment of the volume of blood loss during childbirth and the early postpartum period and the risk of complications of neuraxial blockade in patients with and without gestational thrombocytopenia was carried out.It was found that during gestational thrombocytopenia in the perinatal period, there is no decrease in coagulation potential, assessed by the results of coagulography and thromboelastography at a platelet level above 49×109/l. The investigated indicators of hemostasis did not have significant intergroup differences during pregnancy and childbirth. In the group of patients with gestational thrombocytopenia, the volume of blood loss during labor and the postpartum period did not differ from the group without thrombocytopenia, regardless of the method of delivery. The median blood loss after vaginal delivery in group 1 was 225 ml, in group 2 – 250 ml, with abdominal delivery – 572 ml and 386 ml – respectively. In this study, no complications of neuraxial blockade were observed in any of the groups.The results obtained suggest that in patients with gestational thrombocytopenia, even with a significant decrease in platelet content, it is possible to perform neuraxial blockades during labor, taking into account the clinical picture and the absence of coagulation disorders confirmed by thromboelastography.